2017
DOI: 10.3390/rs9111182
|View full text |Cite
|
Sign up to set email alerts
|

Source Parameters of the 2016–2017 Central Italy Earthquake Sequence from the Sentinel-1, ALOS-2 and GPS Data

Abstract: Abstract:In this study, joint inversions of Synthetic Aperture Radar (SAR) and Global Position System (GPS) measurements are used to investigate the source parameters of four Mw > 5 events of the 2016-2017 Central Italy earthquake sequence. The results show that the four events are all associated with a normal fault striking northwest-southeast and dipping southwest. The observations, in all cases, are consistent with slip on a rupture plane, with strike in the range of 157 • to 164 • and dip in the range of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 31 publications
12
37
0
Order By: Relevance
“…Among the numerous models for the rupture geometry of the Norcia source on 30 October 2016, proposed in the literature (Cheloni et al, ; Pizzi et al, ; Liu et al, ; Walters et al, ; Xu et al, ), the observed anisotropic results seem to be according to seismogenic source solution proposed by Scognamiglio et al (). In fact, the strike of ϕ axes follows the boundaries of a source modeled on two separated fault planes; δtn peaks are located in correspondence of the south‐western and the northern edges on the second N210° fault (see supporting material for details)…”
Section: Resultsmentioning
confidence: 78%
“…Among the numerous models for the rupture geometry of the Norcia source on 30 October 2016, proposed in the literature (Cheloni et al, ; Pizzi et al, ; Liu et al, ; Walters et al, ; Xu et al, ), the observed anisotropic results seem to be according to seismogenic source solution proposed by Scognamiglio et al (). In fact, the strike of ϕ axes follows the boundaries of a source modeled on two separated fault planes; δtn peaks are located in correspondence of the south‐western and the northern edges on the second N210° fault (see supporting material for details)…”
Section: Resultsmentioning
confidence: 78%
“…An earthquake rupture is a process of releasing and readjusting stress; accordingly, stress readjustment plays an important role in understanding the seismic hazard in a seismogenic region, as has been reported by many studies [12,32,44,45]. Without taking shallow slip into account, the distributed slip model of the 2018 Hokkaido eastern Iburi earthquake evaluated herein was used to calculate the static Coulomb stress change (∆CSC) on the fault plane and in the periphery of the study region using Coulomb 3.3 software [46,47], in order to understand the transfer of stress from deep to shallow depths and assess the regional seismic hazards.…”
Section: Static Coulomb Stress Changes and Seismic Hazardsmentioning
confidence: 94%
“…Nevertheless, robust constraints on the source parameters and slip distribution inversion Remote Sens. 2019, 11,1667 3 of 20 can be supplied with a high accuracy by near-field geodetic measurements, for example, measurements from GNSS stations, which completely record coseismic displacements and interferometric synthetic aperture radar (InSAR) observations with a good spatial coverage [11,12]. Such high-precision coseismic surface observations can provide a valuable opportunity to determine the orientations of seismogenic faults and to develop a deeper understanding of the focal mechanism of this event.…”
Section: Introductionmentioning
confidence: 99%
“…It ruptured along the northern part of the Mount Vettore fault, the southern portion of which was only partially activated during the 24 August earthquake [8] and was accompanied by numerous aftershocks [13]. Associated slip distribution models all demonstrate a maximum slip exceeding 2.5 m and a concentrated patch of slip located at depths of 0~7 km [8,[12][13][14] corresponding to observed surface fractures [67]. Cheloni et al [8] observed large displacement residuals reaching up to~10 cm within interferograms after jointly inverting the slip along the two segments of the MGVB fault system using GPS and InSAR data.…”
Section: Seismogenic Tectonicsmentioning
confidence: 99%
“…In addition, Chiaraluce et al [13] observed the presence of several shallow antithetic and synthetic faults through the relocation of aftershocks. Xu et al [14] investigated the interactions among the earthquakes through Coulomb failure stress analysis and suggested that the Amatrice earthquake may have triggered the cascading failures of earthquakes along the complex normal fault system.…”
Section: Introductionmentioning
confidence: 99%